Approaching high temperature performance for proton exchange membrane fuel cells with 3D ordered silica/Cs2.5H0.5PW electrolytes - Liang, Cong; Li, Junsheng; Tang, Haolin; Zhang, Huijie; Zhang, Haining; Mu, Pan (Journal of materials chemistry. A, Materials for energy and sustainability, 2014)
Development of new types of proton conducting materials with efficient transport of protons is one of the most important remaining challenges for elevated-temperature proton exchange membrane fuel cells. Herein, we report the design and synthesis of a new type of proton conducting material based on three dimensional ordered macroporous silica (3DOM silica) incorporated with inorganic Cs2.5H0.5PW electrolytes. The highly ordered structure of 3DOM silica provides well inter-connected pathways for efficient proton transport, especially at high operating temperatures. At a doping amount of 90 wt% of Cs2.5H0.5PW, the proton conductivity of the formed composite electrolyte reaches 0.248 S cm−1 at 170 °C and the activation energy is about 5.775 kJ mol−1. The novel electrolytes also showed good stability as well as excellent single cell performance at 170 °C. The results described here demonstrate that the 3DOM silica/Cs2.5H0.5PW electrode has great potential for high temperature proton exchange membrane fuel cell applications.
First published 23 Oct 2013
Gesehen am 20.10.2020